PCV13-vaccinated children still carrying PCV13 additional serotypes show similar carriage density to a control group of PCV7-vaccinated children. Issue 6 (7th February 2017) - Dagan, Ron; Juergens, Christine; Trammel, James; Patterson, Scott; Greenberg, David; Givon-Lavi, Noga; Porat, Nurith; Gruber, William C.; Scott, Daniel A.
Highlights: Limited evidence suggests that PCVs impact vaccine-type carriage density. This double-blind PCV study suggests no impact on vaccine-type carriage density. PCV13 may affect carriage by reducing carrier number but not vaccine-type density. Carriage density may not impact herd effects. Abstract: Background: In addition to reducing vaccine-type nasopharyngeal carriage rates, pneumococcal conjugate vaccines (PCVs) may decrease carriage density in vaccinated individuals still carrying vaccine serotypes. However, reduction of carriage density has not been systematically studied. This study compared the effect of PCV13 versus PCV7 on carriage density of the serotypes in PCV13 that are not included in PCV7. Methods: This randomized, double-blind study was conducted in southern Israel and included Jewish and Bedouin subjects. Per protocol, 881 and 873 infants received PCV13 and PCV7, respectively, at ages 2, 4, 6, and 12 months. Nasopharyngeal cultures at ages 7, 12, 13, 18, and 24 months were plated using the 4-quadrant semiquantitative method and graded 0 (negative) to 4 (growth in all plate quadrants). In this post hoc analysis, the least squares means of cumulative colonization densities per serotype and serotype combination of the total population and each ethnic subpopulation in each vaccine group were calculated, and differences between vaccine groups derived from a linear model. Results: PCV13-vaccinated children still carrying the 6 additional PCV13 serotypes unique to PCV13 showed no significant differences in carriage density compared with the PCV7-vaccinated control group. No differences in carriage density were shown between Jewish and Bedouin subpopulations despite higher carriage rates among Bedouin subjects. Conclusions: Although PCV13 vaccination reduces vaccine-type carriage compared with PCV7 vaccination by reducing nasopharyngeal acquisition of the additional PCV13 serotypes as previously reported, the current study lacks evidence of a decrease in carriage density of these serotypes when acquired in vaccinated children. Despite the lack of effect on carriage density observed, surveillance data suggest a dramatic decrease in disease rates after PCV implementation. Thus, the current analysis suggests that PCV's impact on carriage density has minimal or no impact on vaccine success. (www.ClinicalTrials.gov : NCT00508742)